Faith in God as a Psychic Factor in the Individual's Spiritual Well-Being ..... - Viktor Moskalets (Vasyl Stefanyk Precarpathian National University, 2017)
The analysis of the human's position in the modern world suggests that faith in God is a vital factor in the state of their spiritual well-being and consequently the strategic paradigm for all forms of psychological help. For the unbiased mind, the miracles of grace and the axiological truth of the humanistic religions are convincing arguments in favour of choosing faith in God. They are evidence that the existence of this world, the being of humanity are blessed with meaning and purpose. An effective strategy in helping a person to shape their dispositional stance after they have rationally accepted faith in God is to emphasize a significant aspect of the true 'fear of God' - the one who believes in afterlife does not want to find themselves in Hell for their sins; it forms the psychological basis of compliance with religious moral guidelines.